6 - Theatre for Development: An Alternative Programme for Reproductive Health Communication in Urban Nigeria - Charles Emeka Nwadigwe (African Sociological Review, 2013)
Communication and public education is vital in reproductive health. It enables awareness of disease, emergent infections, safety and preventive measures. However, health communication programmes in urban Nigeria is faced with a lot of problems among which is the wrong choice of media channels which results in the message not reaching the targeted population. This paper explores the use of Theatre for Development (TfD) as an alternative and complementary medium for communicating reproductive health information to urban dwellers in Nigeria. Using some completed and ongoing health communication projects in Nigeria for illustration, the study seeks to open a forum for dialogue and debate and to draw the attention of policy makers and health workers to exploit the potentials of TfD in combating the challenges of healthcare in urban settings on the continent.